Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Influence of SCR system on the emission characteristics of condensable particulate matter on a 50 kW self-sustaining combustion furnace - Zhengkang Peng; Ling Ai; Hanxiao Liu; Xun Gong; Minghou Xu (Fuel, 2026)

Nanoconfined cerium oxide in a gel-type anion exchanger for efficient fluoride removal from acidic water - Xinwei Zhang; Zhanxun Chen; Mengyi Xu; Ling Yu; Ziyu Wang; Jieyi Ai; Chenghan Ji; Zhuoyao Fang; Xiaolin Zhang (Chemical Engineering Journal, 2026)

Characterization and cellularity of myofibers during early development of Magalobrama amblycephala - Ai-Jin Wang; Meng-Ya Zhang; Ye-Zi Jin; Ke-Cheng Zhu; Hong Liu; Ze-Xia Gao; Huan-Ling Wang (Fish Physiology and Biochemistry, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Rolled-up monolayer MoS2 moiré superlattices for enhanced hydrogen evolution reaction - Ai Wang; Shujin Guo; Yupeng Xie; Haoyang Cheng; Duo Huang; Haoyang He; Yangzhen Jiang; Mao Wang; Hanwen Zhang; Ling Li; Shuopei Wang; Jianqi Zhu (Chemical Engineering Journal, 2026)

Multifunctional layer coupling in hybrid carbon nanotube networks enables high-performance catalyst layer in proton exchange membrane fuel cell - Ling Ai; Ziyu Zhao; Yiheng Xiao; William Talbott; Zeyu Zhou; Xiaochen Yang; Zhiming Feng; Carmine D'Agostino; Sarah Haigh; Maria Perez-Page; Heng Zhai; Stuart M. Holmes (Chemical Engineering Journal, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Synergistic multi-heterointerface engineering of nanocomposite oxide fuel electrodes for highly active and durable high-temperature CO2 electrolysis - Jiaqi Qian; Binbin Hu; Zhiyi Chen; Jiongyuan Huang; Haipeng Zhang; Zixiang Cheng; Na Ai; Ling Zhao; Xin Wang; Yanqun Shao; San Ping Jiang; Dong Tian; et al. (Chemical Engineering Journal, 2026)

Modelling renewable energy effects on biodiversity loss: new evidence from negative binomial regression - Ai-Lian Tan; Chee-Loong Lee; Yan-Ling Tan; Thian-Hee Yiew (Environment, Development and Sustainability, 2026)

Epimedium polysaccharide alleviates adenine-induced oligoasthenozoospermia in mice by inhibiting ferroptosis and inflammation through TLR4/NF-κB and SLC7A11/GPX4 axis - Kun-Yang Tang; Wang Ai; Xiao-Cui Jiang; Min Xiao; Yan-Yan Zhou; Xiao-Ming Yu; Shu-Hui Chen; Jing-Ling Zhao (Reproductive Biology, 2026)

Identification of common released peptide and allergenic cross-reactivity of protein fractions among cereals - Li Li Xu; Pan Pan Pei; Yu Jie Wang; Ai Zhen Zong; Tong Cheng Xu; Ying Yuan Zhao; Fang Ling Du (Food Chemistry, 2026)

Cellulose nanocrystal-based antimicrobial porous foam loaded with cinnamaldehyde for enhanced chilled meat preservation - Jin-ling Wu; Ai-ling Zhong; Rui Zhang; Hai-yan Huang; Teng-gen Hu; Zhen-lin Xu; Hong Wang; Peng Wen (Food Packaging and Shelf Life, 2026)

Bulk-interface synergetic engineering of nanocomposite air electrode toward durable and high-performance solid oxide cells - Zhiyi Chen; Haipeng Zhang; Wenjia Ma; Jiongyuan Huang; Jiaqi Qian; Meihuang Liu; Dong Tian; Na Ai; Pei Yuan; San Ping Jiang; Ling Zhao; Zongping Shao; et al. (Chemical Engineering Journal, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Correction to: Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Eight weeks after anthesis: a critical fruit developmental stage for tissue-border establishment in oil palm tenera fruit - Fong-Chin Lee; Wan-Chin Yeap; Po-Yee Fong; Ai-Ling Ong; Chee-Keng Teh (Protoplasma, 2026)

Viruses regulate soil C:N stoichiometry by boosting C-cycling under long-term N fertilization - Hanpeng Liao; Chen Liu; Tian Gao; Chaofan Ai; Ning Ling; Shuping Qin; Chunsheng Hu; Dong Zhang; Xiang Tang; Ville-Petri Friman; Shungui Zhou (Soil Biology and Biochemistry, 2026)

An end-to-end reactive oxygen species scavenger for targeted therapy of myocardial ischemia-reperfusion injury by concurrently eliminating superoxide anion and hydroxyl radical - Shuya Wang; Yuting Lin; Tianjiao Zhao; Xiaojing Shi; Tingli Xiong; Ruishi Li; Wenxuan Zheng; Min Liu; Fei Li; Jiawen Wei; Ling Yang; Qiong Huang; et al. (Chemical Engineering Journal, 2026)

Imaging the northern Zagros collision zone by ambient noise and earthquake surface wave tomography - Zahra Zarunizadeh; Abdelkrim Aoudia; Khalil Motaghi; Surya Pachhai; Daniel Manu-Marfo; Yingjie Yang; Wathiq Abdulnaby; Yinshuang Ai; Ling Chen (Tectonophysics, 2026)

Enzymatic stoichiometry as a reliable proxy for evaluating microbial nutrient limitation in lentic sediments and phosphorus-enriched soils: A meta-analysis - Ling AI; Ting QING; Fuzhong WU; Meilin XUAN; Kai YUE; Xiangyin NI (Pedosphere, 2026)

Localized nitrate uptake by NRT1.8 antagonizes root meristem growth inhibition upon cadmium stress - Ling-Ling Wang; Fang-Chang Ling; Zi-Ai Qi; Zi-Jun Fang; Hui Li; Ji-Ming Gong (Journal of Hazardous Materials, 2026)

Lattice engineering of Li1.6Mn1.6O4 adsorbent materials mitigates Jahn-Teller distortion for efficient and stable lithium extraction from brine - Lu-Ri Bao; Zhi Ai Huang; Ling Zang; Wei Ping Tang; Shu-Ying Sun (Chemical Engineering Journal, 2026)

Effective extraction of phosphate from strongly acidic wastewater using applicable nanocomposite containing highly reactive titanium oxides with excellent stability - Zhanxun Chen; Mengyi Xu; Ziyu Wang; Ling Yu; Jieyi Ai; Chenghan Ji; Zhuoyao Fang; Xiaolin Zhang (Chemical Engineering Journal, 2026)

Geochemical signatures of mud and core gases from the Milun Fault Scientific Drilling (MiDAS), Taiwan: Implications for fluid pathways and crustal degassing - Ching-Chou Fu; Kuo-Hang Chen; Kuo-Wei Wu; Pei-Ling Wang; Ai-Ti Chen; Vivek Walia; Kuo-Fong Ma (Chemical Geology, 2026)

Effects of phyllosphere and rhizosphere microbes on intraspecific competition of the invasive plant Ageratina adenophora and native plants - Zi-Qing Liu; Zhao-Ying Zeng; Ai-Ling Yang; Yong-Lan Wang; Chao Zhao; Han-Bo Zhang (Plant and Soil, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Near-surface geothermal reservoir exploration by multichannel analysis of passive surface waves using urban traffic noise in Shanxi - Ling Ning; Tianyu Dai; Guoshu Huang; Liang Liu; Hanbing Ai; Chaoqiang Xi (Journal of Applied Geophysics, 2026)

Cu3P electrode catalyze degradations of metronidazole and chloramphenicol fast in high-amount Cl− over broad pH - Ruanshan Liu; Ling Zhang; Yuhe Shi; Guichuan Wei; Fanfan Guo; Yifan Wang; Bin Liang; Jing-Long Han; Ai Jie Wang (Chemical Engineering Journal, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Porcine reproductive and respiratory syndrome virus downregulates the circ-107191/miR-34c/RAD54L axis to promote testicular cell apoptosis via impaired homologous recombination repair - Bingzhou Huang; Dong You; Baoling Liu; Siyuan Lai; Yanru Ai; Jianbo Huang; Yuancheng Zhou; Liangpeng Ge; Xiu Zeng; Zhiwen Xu; Ling Zhu (Theriogenology, 2025)

Three tetraspanins, Tspan1, Tspan2A and Tspan3 from Litopenaeus vannamei involved into Vibrio parahaemolyticus infection - Yi-Qian Zhang; Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Chao-Jie Hou; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Yan Lei; Wei-Lin Zhu; Hong Liu; Yong-Zhen Zhao; et al. (Fish & Shellfish Immunology, 2025)

Single nucleotide variations triggered responsive strip for Helicobacter pylori theranostics - Lin-Min Zhong; Qi-Ling Yang; Xin-Yi Zhong; Xiao-Rong Zhang; Fen-Ying Kong; Shan-Wen Hu; Ai-Lin Liu (Chemical Engineering Journal, 2025)

Genome-Wide Identification of Pitaya (Hylocereus polyrhizus) TCPs and their Involvement in Flower Development and Abiotic Stress Response - Ling Xiao; Xiaowei Cai; Runrun Yu; Xiangmei Nie; Ai-Hua Wang; Kun Yang; Xiaopeng Wen (Tropical Plant Biology, 2025)

Probiotics reduce the severity of DSS-induced colitis in aged mice by enhancing intestinal barrier function and modulating gut microbiota - Ai-Ling Liu; Hong Lv; Hong-Ying Wang; Hong Yang; Yue Li; Yan-Fang Jia; Jia-Ming Qian (GeroScience, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Humic substances initiated superior photochemical pollutant conversion in environmentally relevant matrices: When ZnO met MoS2 as electron mediator - Jia-Sheng Li; Song Hu; Ling-Feng Wang; Wei Da; Ai-Yong Zhang; Lu Zhao; Jing-Yu Zhang (Journal of Environmental Chemical Engineering, 2025)

Transdimensional joint inversion of surface wave, refraction, and resistivity data using Modified Barnacles Mating Optimizer for near-surface investigations - Hanbing Ai; Xianhai Song; Xueqiang Zhang; Yunus Levent Ekinci; Çağlayan Balkaya; Arka Roy; Jiazhe Li; Ling Ning; Zhao Le; Yingwei Yan (Journal of Applied Geophysics, 2025)

Concrete-inspired injectable microspheres/ hydrogel composite system for sustained release stem-cell secretome and long-term soft tissue filling - You-Yu Duan; Bai-Hua Liao; Wan-Ling Huang; Wei-Huang Wang; Ranjith Kumar Kankala; Shi-Bin Wang; Pei-Yao Xu; Ai-Zheng Chen (Chemical Engineering Journal, 2025)

Enhancing ECL efficiency of tris (bipyridine) ruthenium via amino-group-tuned Pd-MOFs for competitive detection of glypican-3 - Ling-Yi Su; Wen Liu; Jing-Yi Bao; Ai-Jun Wang; Pei-Xin Yuan; Jiu-Ju Feng (Analytica Chimica Acta, 2025)

Microbial synergistic metabolic mechanism of enhanced tetrabromobisphenol A removal by bio-electrochemical system coupled constructed wetland - Xiao-Qiu Lin; Zhi-Ling Li; Xue-Qi Chen; Ling Wang; Lan Yu; Ai-Jie Wang (Journal of Hazardous Materials, 2025)

Mineralogical and chronological records of strong shock metamorphism in pigeonite cumulate eucrite Northwest Africa 8326 - Lang Zhang; Ai-Cheng Zhang; Xiao-Wen Liu; Yan-Jun Guo; Jia-Ni Chen; Yuan-Yun Wen; Qiu-Li Li; Yu Liu; Xiao-Xiao Ling; Jin S. Zhang (Geochimica et Cosmochimica Acta, 2025)

Engineering Long-Acting apixaban loaded PLGA microspheres for the treatment of stroke caused by atrial fibrillation - Xue-Ai Liu; Yaseen Hussain; Jiawen Wang; Ping Xia; Xiang-Xiang Huang; Ming-Wei Huo; Ling-Zhi Shi; Jing-Hao Cui; Beom-Jin Lee; Renyu Huang; Yujin Ji; Minggang Wei; et al. (Chemical Engineering Journal, 2025)

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Simultaneous high molecular weight PAHs degradation and chromate and arsenite detoxification by Altererythrobacter sp. H2 - Qun Han; Mei-Ling Yang; Ze-Shen Liu; Ying-Hao Zhao; Xue-Hui Liu; Guo-Min Ai; Wei-Hong Qin; Xing-Yu Liu; De-Feng Li (Journal of Hazardous Materials, 2025)

Variations in 3-chloropropanol esters, glycidyl esters, and lipid accompaniments during the simulated moderate decolorization process of maize germ oil - Yu Jie Wang; Li Li Xu; Ai Zhen Zong; Fang Ling Du; Deng Yu Xie; Yun Qi Wen; Tong Cheng Xu (Food Chemistry, 2025)

Quality analysis of AIS data derived from Haiyang (HY) series satellites - Xi Ding; Songtao Ai; Jiajun Ling; Meng Cui; Jiachun An; Lei Huang (Acta Oceanologica Sinica, 2025)

Identification and characterization of oxygen- and bile salt-inducible promoters in Lactiplantibacillus plantarum AR113 for probiotic applications - Feng Xin; Wang Guangqiang; Chen Yunhui; Xiong Zhiqiang; Xia Yongjun; Nan Zhao; Wenwen Lu; Ling Ni; Ying Zhou; Ai lianzhong (Food Bioscience, 2025)

Mitigating chromium attack of cathode for durable solid oxide fuel cells through a strain regulation strategy - Jiongyuan Huang; Jiaqi Qian; Cheng Cheng Wang; Zhiyi Chen; Haipeng Zhang; Zixiang Cheng; Ling Zhao; Na Ai; Chengzhi Guan; Yanqun Shao; San Ping Jiang; Kongfa Chen (Chemical Engineering Journal, 2025)

Transcriptomic analysis of wrinkled leaf development of Tai-cai (Brassica rapa var. tai-tsai) and its synthetic allotetraploid via RNA and miRNA sequencing - Xinli Zhang; Wen Zheng; Zhiyu Zhu; Xiaocan Guo; Jinbao Hu; Li’ai Xu; Huihui Fang; Yunshuai Huang; Zhengyan Ling; Zhujun Zhu; Yunxiang Zang; Jianguo Wu (Plant Molecular Biology, 2025)

Slowing wind increases soil carbon emissions in a fragmented subtropical forest: a study combining field and model experiments - Hao-Hao Wu; Ling-Ling Zhang; Ai-Min Liao; Hua-Wu Wu; Xiao-Ming Lai; Hai-Xia Zhang; Ye Xia; Yang Cao; Zi-Chun Zhu; Zhen-Ming Ji; Cong-Sheng Fu (Plant and Soil, 2025)

Exogenous NaHS maintains storage quality of Prunus salicina ‘Wushan plum’ by regulating the antioxidant system, endogenous H2S, ethylene and NO metabolism - Saiying Han; Ling Liu; Lilei Wang; Jin Han; Yeru Ai; Huali Wang; Kaifang Zeng; Jian Ming; Lili Deng (Postharvest Biology and Technology, 2025)

Bacteria-supported manganese oxide for enhanced fluoroquinolone antibiotics removal in peroxymonosulfate oxidation system - Ling Zhu; Yuan-Yuan Chu; Fei Liu; Kai-Yan Ai; Wen-Wen Xu; Yuan-Yuan Cheng; Chao Wu; Liu-Gen Zheng (Environmental Research, 2025)

Extracellular electron transfer-dependent bioremediation of uranium-contaminated groundwater: Advancements and challenges - Zhi-Ling Li; Sheng-Fang Li; Zi-Meng Zhang; Xue-Qi Chen; Xi-Qi Li; Yun-Xia Zu; Fan Chen; Ai-Jie Wang (Water Research, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Optimized near infrared reflectance model based on preprocessing selection strategy for rapid analysis of 2-acetyl-1-pyrroline content in rice flour - Li-Hong Xie; Shao-Qing Tang; Gao-Neng Shao; Zhong-Hua Sheng; Shi-Kai Hu; Xiang-Jin Wei; Gui-Ai Jiao; Ling Wang; Pei-Song Hu (Food Control, 2025)

Permafrost environment evaluation of Qinghai-Tibetan Plateau based on DPSRC theory and system dynamics - Yi-Ning Ye; Ya-Ling Chou; Dong Zhao; Wei Cao; Jia-Wei Xu; Ai-Jun Wang (Ecological Modelling, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

Petrogenesis of the unbrecciated pigeonite cumulate eucrite Northwest Africa 8326: Bridging the gap between eucrites and diogenites - Xiao-Wen Liu; Ai-Cheng Zhang; Li-Hui Chen; Lang Zhang; Xiao-Jun Wang; Jia Liu; Li-Ping Qin; Yu Liu; Qiu-Li Li; Xiao-Xiao Ling (Geochimica et Cosmochimica Acta, 2025)

Elevated CO2 alters antibiotic resistome in soil amended with sulfamethazine via chemical-organic fertilization - Fen Xu; Qian Xiang; Mei-Ling Xu; Laura J. Carter; Wen-Chao Du; Chun-Wu Zhu; Fu-Xun Ai; Ying Yin; Rong Ji; Hong-Yan Guo (Environmental Research, 2025)

Simultaneous deep removal of nitrate and tetrabromobisphenol A in microbial electrochemical system-constructed wetland - Xiao-Qiu Lin; Zhi-Ling Li; Xue-Qi Chen; Ling Wang; Ai-Jie Wang (Bioresource Technology, 2025)

Exploring the potential use of Caenorhabditis elegans as an animal model for evaluating chemical-induced intestinal dysfunction - Xiao-Pan Zhang; Xuan Ma; Jun-Ling Liu; Ai-Lin Liu (Toxicology and Applied Pharmacology, 2024)

Bearing performance and failure mechanisms of HSCM piles in marine soft soil under lateral loads - Hang Cen; Jun-nan Zhao; Zhong-ling Zong; De-long Huang; Ding-wen Zhang; Hui-yue Wang; Ai-ping Tang (Ocean Engineering, 2024)

Disease risk of the foliar endophyte Colletotrichum from invasive Ageratina adenophora to native plants and crops - Ai-Ling Yang; Yi-Shan Chen; Liang Mei; Jing Guo; Han-Bo Zhang (Fungal Ecology, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Identification, functional analysis of chitin-binding proteins and the association of its single nucleotide polymorphisms with Vibrio parahaemolyticus resistance in Penaeus vannamei - Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Di-Gang Zeng; Yong-Zhen Zhao; Huan-Ling Wang (Fish & Shellfish Immunology, 2024)

Metabolism of isodecyl diphenyl phosphate in rice and microbiome system: Differential metabolic pathways and underlying mechanisms - Yuanyuan Yu; Tao Ai; Jiahui Huang; Ling Jin; Xiaolong Yu; Xifen Zhu; Jianteng Sun; Lizhong Zhu (Environmental Pollution, 2024)

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Influence and mechanism of typical transition metal ions on the denitrification performance of heterotrophic nitrification-aerobic denitrification bacteria - Yun-chun Shi; Fan Gou; Ai-ling Chen; Zhi-lin Xing; Qian Zhang; Heng Wu; Tian-tao Zhao (Environmental Research, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

SIRT1 regulates mitochondrial fission to alleviate high altitude hypoxia inducedcardiac dysfunction in rats via the PGC-1α-DRP1/FIS1/MFF pathway - Hongbao Xu; Xiaona Song; Xiaoru Zhang; Guangrui Wang; Xiaoling Cheng; Ling Zhang; Zirou Wang; Ran Li; Chongyi Ai; Xinxing Wang; Lingling Pu; Zhaoli Chen; et al. (Apoptosis, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Simplified Calculation of Earthquake Energy Transfer of Different Pipe Supports Inside Utility Tunnel at Horizontal Non-Homogeneous Field - De-long Huang; Hang Cen; Jin Wang; Hui-yue Wang; Qiang Liu; Zhong-ling Zong; Ai-ping Tang; Song-ling Xue (Geotechnical and Geological Engineering, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Regulating microbial redox reactions towards enhanced removal of refractory organic nitrogen from wastewater - Ke Shi; Bin Liang; Hao-Yi Cheng; Hong-Cheng Wang; Wen-Zong Liu; Zhi-Ling Li; Jing-Long Han; Shu-Hong Gao; Ai-Jie Wang (Water Research, 2024)

Study of the dynamic interactions between helix-stiffened cement mixing piles and soft soil under oblique incidence of SV waves in arbitrary space - Hang Cen; Zhong-ling Zong; De-long Huang; Hui-yue Wang; Xiao-xuan Zhuang; Zi-yuan Huang; Ai-ping Tang (Computers and Geotechnics, 2024)

In-situ constructed interface buffer layer enabled highly reversible Zn Deposition/Stripping for long-lifespan aqueous zinc metal anodes - Li Zhou; Weibin Zhou; Hongrui Wang; Qi Deng; Xingtong Ai; Xian-Xiang Zeng; Xiongwei Wu; Congshan Zhou; Wei Ling (Chemical Engineering Journal, 2024)

Comparison of Mycoplasma pneumoniae infection in children admitted with community acquired pneumonia before and during the COVID-19 pandemic: a retrospective study at a tertiary hospital of southwest China - Ling Ai; Beizhong Liu; Liang Fang; Chanjuan Zhou; Fang Gong (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Historical catastrophic floods at the southern edge of the Atacama Desert: A multi-archive reconstruction of the Copiapó river extreme events - Tatiana Izquierdo; Ai-ling Rivera; Ángela Galeano; Diego Gallardo; Verónica Salas; Olga Aparicio; Jan-Pieter Buylaert; Francisco Ruiz; Manuel Abad (Global and Planetary Change, 2024)

Two thin middle-crust low-velocity zones imaged in the Chuan-Dian region of southeastern Tibetan Plateau and their tectonic implications - Long Li; Xin Wang; Guangbing Hou; Yuan Ling; Yinshuang Ai (Science China Earth Sciences, 2024)

Polyethyleneimine functionalized gold nanodendrites for gluconic acid electroreduction - Zhe Wang; Qing-Ling Hong; Zhou-Yingqi Qu; Feng Shi; Chong Zhang; Pu-Jun Jin; Pei Chen; Xuan Ai; Yu Chen (Chemical Engineering Journal, 2024)

Ultrasonic-assisted synthesis of CaCu3Ti4O12/reduced graphene oxide composites for enhanced photocatalytic degradation of pharmaceutical products: Ibuprofen and Ciprofloxacin - Mohsen Ahmadipour; Mohammad Rezaei Ardani; Mohsen Sarafbidabad; Nadhem Missaoui; Meenaloshini Satgunam; Ramesh Singh; Hamza Kahri; Ujjwal Pal; Ai Ling Pang; Muhammad Saqlain Iqbal; Renuka Garg; Anish Bhattacharya (Environmental Science and Pollution Research, 2024)

The construction and immunogenicity analyses of a recombinant pseudorabies virus with Senecavirus A VP3 protein co-expression - Qian Tao; Lei Xu; Yang Zhang; Yanting Yang; Zheyan Liu; Tong Xu; Siyuan Lai; Yanru Ai; Ling Zhu; Zhiwen Xu (Veterinary Microbiology, 2024)

Transformation process and phytotoxicity of sulfamethoxazole and N4-acetyl-sulfamethoxazole in rice - Tao Ai; Siyu Yao; Yuanyuan Yu; Kai Peng; Ling Jin; Xifen Zhu; Haijun Zhou; Jiahui Huang; Jianteng Sun; Lizhong Zhu (Science of The Total Environment, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Dietary supplementation of patchouli oil improves resistance to Streptococcus agalactiae infection in genetically improved cultured Tilapia (GIFT, Oreochromis niloticus.) as revealed by RNA-Seq - Yin Yi Yao; Zong Xian Zhu; Chun Hui Ai; Xue Ying Liang; Gan Yang; Tong De Liu; Hong Yi Zhang; Han Jing Yan; Jun Hong Xia; Meng Ling He (Aquaculture, 2024)

Thin film composite polyamide nanofiltration membranes with interlayer constructed with core-shell structured polystyrene-polyacrylamide nanospheres for antibiotics separation - Ben-Qing Huang; Hong-Guang Cui; Tian-Yun Feng; Cai-Ling Yuan; Ai-Lian Chang; Ming-Lu Shao; Chi-Fan Zhu (Journal of Water Process Engineering, 2024)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Litter traps: A comparison of four marine habitats as sinks for anthropogenic marine macro-litter in Singapore - Jenny Fong; Samuel Hsien Rong Lee; Yuchen Sun; Cheng Ling Lim; Yean Ai Jolin Tan; Yi Hong Tan; Mei Lin Neo (Marine Pollution Bulletin, 2023)

Immunogenic response of recombinant pseudorabies virus carrying B646L and B602L genes of African swine fever virus in mice - Lishuang Deng; Sirui Gu; Yao Huang; Yuling Wang; Jun Zhao; Mincai Nie; Lei Xu; Siyuan Lai; Yanru Ai; Zhiwen Xu; Ling Zhu (Veterinary Microbiology, 2023)

In vivo antibacterial activity of medicinal plant Sophora flavescens against Streptococcus agalactiae infection - Fa‐Li Zhang; Liu Yang; Wei‐Hao He; Ling‐Jun Xie; Fei Yang; Ying‐Hui Wang; Ai‐Guo Huang (Journal of Fish Diseases, 2023)
Streptococcosis disease caused by Streptococcus agalactiae (Group B Streptococcus, GBS) results in a huge economic loss of tilapia culture. It is urgent to find new antimicrobial agents against streptococcosis. In this study, 20 medicinal plants were evaluated in vitro and in vivo to obtain medicinal plants and potential bioactive compounds against GBS infection. The results showed that the ethanol extracts of 20 medicinal plants had low or no antibacterial properties in vitro, with a minimal inhibitory concentration ≥256 mg/L. Interestingly, in vivo tests showed that 7 medicinal plants could significantly inhibit GBS infection in tilapia, and Sophora flavescens (SF) had the strongest anti‐GBS activity in tilapia, reaching 92.68%. SF could significantly reduce the bacterial loads of GBS in different tissues (liver, spleen and brain) of tilapia after treated with different tested concentrations (12.5, 25.0, 50.0 and 100.0 mg/kg) for 24 h. Moreover, 50 mg/kg SF could significantly improve the survival rate of GBS‐infected tilapia by inhibiting GBS replication. Furthermore, the expression of antioxidant gene cat , immune‐related gene c‐type lysozyme and anti‐inflammatory cytokine il‐10 in liver tissue of GBS‐infected tilapia significantly increased after treated with SF for 24 h. Meanwhile, SF significantly reduced the expression of immune‐related gene myd88 and pro‐inflammatory cytokines il‐8 and il‐1β in liver tissue of GBS‐infected tilapia. The negative and positive models of UPLC‐QE‐MS, respectively, identified 27 and 57 components of SF. The major components of SF extract in the negative model were α, α‐trehalose, DL‐malic acid, D‐ (−)‐fructose and xanthohumol, while in the positive model were oxymatrine, formononetin, (−)‐maackiain and xanthohumol. Interestingly, oxymatrine and xanthohumol could significantly inhibit GBS infection in tilapia. Taken together, these results suggest that SF can inhibit GBS infection in tilapia, and it has potential for the development of anti‐GBS agents.

Pyrite coupled with steel slag to enhance simultaneous nitrogen and phosphorus removal in constructed wetlands - Ying Liu; Xiao-Hui Liu; Hong-Cheng Wang; Zhi-Ling Li; Bin Liang; Yi-Lu Sun; Hao-Yi Cheng; Shao-Yong Lu; Ai-Jie Wang (Chemical Engineering Journal, 2023)

The regulating role of applied voltage on methanogenesis in an up-flow single-chamber microbial electrolysis assisted reactor - Lei Gao; Thangavel Sangeetha; Ling Wang; Min-Hua Cui; Ze-Chong Guo; Wei-Mon Yan; Wen-Zong Liu; Ai-Jie Wang (Journal of Water Process Engineering, 2023)

The potential of functionalized graphene-based composites for removing heavy metals and organic pollutants - Muhammad Saqlain Iqbal; Awais Ali Aslam; Ramsha Iftikhar; Muhammad Junaid; Syed Muhammad Imran; Muhammad Shahid Nazir; Zulfiqar Ali; Muhammad Zafar; Ayesha Kanwal; Norinsan Kamil Othman; Ujjwal Pal; Ai Ling Pang; et al. (Journal of Water Process Engineering, 2023)

In situ growth of flower sphere Bi2WO6/Bi-MOF heterojunction with enhanced photocatalytic degradation of pollutants: DFT calculation and mechanism - Yusheng Yang; Mengjiao Xu; Lili Ai; Nannan Guo; Changyu Leng; Chuan Tan; Min Lu; Luxiang Wang; Ling Huang; Dianzeng Jia (Journal of Environmental Chemical Engineering, 2023)

Boosting diethylamine selective oxidation over CuO/ZSM-5 catalyst by CeO2 modification - Lin-Cong He; Hua-Hui Xu; Xing-Yue Leng; Ling-Yun Jin; Ai-Ping Jia; Meng-Fei Luo; Jian Chen (Fuel, 2023)

Topographic hydro-conditioning to resolve surface depression storage and ponding in a fully distributed hydrologic model - Ai-Ling Jiang; Kuolin Hsu; Brett F. Sanders; Soroosh Sorooshian (Advances in Water Resources, 2023)

Oxalated zero valent iron enables highly efficient heterogeneous Fenton reaction by self-adapting pH and accelerating proton cycle - Xu Zhang; Hongwei Sun; Yanbiao Shi; Cancan Ling; Meiqi Li; Chuan Liang; Falong Jia; Xiao Liu; Lizhi Zhang; Zhihui Ai (Water Research, 2023)

Rapid screening of diarylpentanoids from Daphne bholua - Shu-Hui Dong; Mei-Ya Lian; Jin-Ling Han; Yun-Fei Ai; Xiao-Fang Zhou; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Identifying the critical areas and primary sources for agricultural non-point source pollution management of an emigrant town within the Three Gorges reservoir area - Wen Xu; Ling Liu; Shi-jiang Zhu; Ai-hua Sun; Hao Wang; Zhi-yu Ding (Environmental Monitoring and Assessment, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Immunization effect of recombinant Lactobacillus casei displaying Aeromonas veronii Aha1 with an LTB adjuvant in carp - Xue Jiao; Dong-Xing Zhang; Chong Chen; Ling-cong Kong; Xiao-Yu Hu; Xiao-Feng Shan; Ai-Dong Qian (Fish & Shellfish Immunology, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Two Novel Species of Mesophoma gen. nov. from China - Ai-Ling Yang; Lin Chen; Lu Cheng; Jin-Peng Li; Zhao-Ying Zeng; Han-Bo Zhang (Current Microbiology, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Effect of temperature on the life table parameters and high-temperature lethality of Tyrophagus putrescentiae - Peipei Zhu; Shan Yang; Yuanfa Yang; Hui Ai; Mingfang Chen; Xi Wang; Ling Zhong; Bin Xia; Zhiwen Zou (Journal of Stored Products Research, 2023)

Different effects of litter and root inputs on soil enzyme activities in terrestrial ecosystems - Ling Ai; Fuzhong Wu; Xuebo Fan; Ying Yang; Yu Zhang; Xiaping Zheng; Jingjing Zhu; Xiangyin Ni (Applied Soil Ecology, 2023)

Cathode potential regulates the microbiome assembly and function in electrostimulated bio- dechlorination system - Di Cao; Zhi-Ling Li; Ke Shi; Bin Liang; Zhongli Zhu; Wenzong Liu; Jun Nan; Kai Sun; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Small organic molecules as fluorescent sensors for the detection of highly toxic heavy metal cations in portable water - Ramsha Iftikhar; Iqra Parveen; Ayesha; Aqsa Mazhar; Muhammad Saqlain Iqbal; Ghulam Mustafa Kamal; Freeha Hafeez; Ai Ling Pang; Mohsen Ahmadipour (Journal of Environmental Chemical Engineering, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Pyrolysis temperature-switchable Fe-N sites in pharmaceutical sludge biochar toward peroxymonosulfate activation for efficient pollutants degradation - Chuan Liang; Hongwei Sun; Cancan Ling; Xiufan Liu; Meiqi Li; Xiang Zhang; Furong Guo; Xu Zhang; Yanbiao Shi; Shiyu Cao; Hua He; Zhihui Ai; et al. (Water Research, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Vandachostylis ‘Sri-Siam’: an intergeneric hybrid with superior qualities as evidenced by its biochemical fragrance and transcriptome profiles - Ab Rahim Mohd-Hairul; Janna Ong-Abdullah; Adelene Ai-Lian Song; Hooi Ling Foo; Parameswari Namasivayam; Raha Abdul Rahim (Journal of Plant Biochemistry and Biotechnology, 2022)

Carbon dioxide electroreduction into formic acid and ethylene: a review - Ling Ai; Sue-Faye Ng; Wee-Jun Ong (Environmental Chemistry Letters, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Environmental Kuznets curve for biodiversity loss: evidence from South and Southeast Asian countries - Yan-Ling Tan; Thian-Hee Yiew; Lin-Sea Lau; Ai-Lian Tan (Environmental Science and Pollution Research, 2022)

Extended Middle Cerebral Artery Occlusion (MCAO) Model to Mirror Stroke Patients Undergoing Thrombectomy - Sarah J. Messmer; Kathleen E. Salmeron; Jacqueline A. Frank; Christopher J. McLouth; Douglas E. Lukins; Tyler C. Hammond; Ai-Ling Lin; Justin F. Fraser; Keith R. Pennypacker (Translational Stroke Research, 2022)

Isolation and characterization of AaZFP1, a C2H2 zinc finger protein that regulates the AaIPPI1 gene involved in artemisinin biosynthesis in Artemisia annua - Yin-ai Deng; Li Li; Qian Peng; Ling-fang Feng; Jin-fen Yang; Ruo-ting Zhan; Dong-ming Ma (Planta, 2022)

Isolation and Characterization of a Novel Lytic Halotolerant Phage from Yuncheng Saline Lake - Chuan-Xu Wang; Ai-Hua Zhao; Hui-Ying Yu; Ling-Li Wang; Xin Li (Indian Journal of Microbiology, 2022)

Crustal thickness and composition in the South China Block: Constraints from earthquake receiver function - Changxin Chen; Qingtian Lü; Ling Chen; Danian Shi; Jiayong Yan; Yinshuang Ai (Science China Earth Sciences, 2022)

Volatile constituents and floral transcriptome analyses provide new insights into fragrance biosynthesis of Vanda ‘Tan Chay Yan’ - Ab. Rahim Mohd-Hairul; Janna Ong Abdullah; Adelene Ai Lian Song; Hooi Ling Foo; Parameswari Namasivayam; Raha Abdul Rahim (Plant Biosystems, 2022)

Lactate anions participate in T cell cytokine production and function - Jing Wen; Shipeng Cheng; Yaguang Zhang; Ran Wang; Jiefang Xu; Zhiyang Ling; Liyan Ma; Xinghao Ai; Bing Sun (Science China Life Sciences, 2021)

Four genetic loci affecting swine lung lesions identified by whole-genome sequencing-based association studies - Xinkai Tong; Tao Huang; Mingpeng Zhang; Jiaqi Chen; Zhou Zhang; Jingquan Li; Huipeng Du; Ziqi Ling; Zhongzi Wu; Bin Yang; Shijun Xiao; Huashui Ai (Science China Life Sciences, 2021)

Dose-Dependent Effects of Histamine on Growth, Immunity and Intestinal Health in Juvenile Grouper (Epinephelus coioides) - Zi-Yan Liu; Hong-Ling Yang; Ling-Hao Hu; Wei Yang; Chun-Xiang Ai; Yun-Zhang Sun (Frontiers in Marine Science, 2021)
A 56 day feeding trial was conducted to examine the effects of different levels of dietary histamine on growth performance, immune response, and intestinal health of grouper ( Epinephelus coioides ). Seven isonitrogenous (46%), isolipidic (10%) diets were prepared with histamine supplement levels of 0 (T0), 0.05% (T1), 0.1% (T2), 0.15% (T3), 0.2% (T4), 0.25% (T5), and 0.3% (T6), respectively. The results showed that histamine supplementation had no significant effects on weight gain rate (WGR), specific growth rate (SGR), feed conversion rate (FCR), hepatosomatic index (HSI), and survival rate (SR) at the initial feeding period (day 0–28), but WGR and SGR had negative linear responses to the dietary histamine level at the whole feeding period (day 0–56), and a significant decrease was observed in groups T5 and T6 compared with T0 ( P < 0.05). Supplementation of histamine decreased antioxidant capacity, immune response, the contents of serum interleukin-1 beta (IL-1β), intestinal-type fatty acid-binding protein (FABP2) and intestinal trefoil factor (ITF), and caused serious damage of intestine with significantly decreased VH and MFH of grouper, especially in fish fed with diets supplemented with high doses of histamine (0.25 and 0.3%). The intestinal microbial communities in treatments were different clearly with the control (T0), in terms of beta (β)-diversity boxplots and UPGMA phylogenetic tree based on unweighted unifrac distance. At the phylum level, the relative abundance of Fusobacteria was lower in group T0, while the abundance of Firmicutes was significantly lower in groups T5 and T6 ( P < 0.05). At the genus level, the relative abundance of uncultured_bacterium_f_ Bacteroidales _S24-7_group, uncultured_bacterium_f_ Lachnospiraceae , and Ruminiclostridium were significantly higher in the control, while the abundance of Cetobacterium was significantly higher in groups T5 and T6 ( P < 0.05). In conclusion, the present study suggested that up to 0.2% of dietary histamine did not result in a remarkable reduction in growth, immune response, and intestinal health; however, 0.25% or more dietary histamine could cause significant negative effects on growth performance, immune response, and intestinal health in E. coioides .

Combined characterization of a new member of Marivita cryptomonadis strain LZ-15-2 isolated from cultivable phycosphere microbiota of highly toxic HAB dinoflagellate Alexandrium catenella LZT09 - Xin Zhou; Xiao-Ai Zhang; Zhi-Wei Jiang; Xi Yang; Xiao-Ling Zhang; Qiao Yang (Brazilian Journal of Microbiology, 2021)

Mitochondrial fusion protein 2 regulates endoplasmic reticulum stress in preeclampsia - Dandan Sun; Hui Zhu; Ling Ai; Hanbing Wu; Yanting Wu; Jihua Jin (Journal of Zhejiang University-SCIENCE B, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

Picea wilsonii NAC Transcription Factor PwNAC30 Negatively Regulates Abiotic Stress Tolerance in Transgenic Arabidopsis - Ke-hao Liang; Ai-bin Wang; Yi-hang Yuan; Ya-hui Miao; Ling-yun Zhang (Plant Molecular Biology Reporter, 2020)

Aerosol microbial community structure analysis based on two different sequencing platforms - Xiu-lu Lang; Ai-ling Xu; Xiang Chen; Zhi-wen Song (Aerobiologia, 2020)

Xanthatin mediates G 2 /M cell cycle arrest, autophagy and apoptosis via ROS/XIAP signaling in human colon cancer cells - Ya-di Geng; Lei Zhang; Guo-Yu Wang; Xiao-Jun Feng; Zhao-Lin Chen; Ling Jiang; Ai-Zong Shen (Natural Product Research, 2020)

Comprehensive evaluation of rural courtyard utilization efficiency: A case study in Shandong Province, Eastern China - Ya-qiu Liu; Ai-ling Wang; Jie Hou; Xin-yu Chen; Jin-shan Xia (Journal of Mountain Science, 2020)

Role of adjuvant (chemo)radiotherapy for resected extrahepatic cholangiocarcinoma: a meta-analysis - Xin-qi Shi; Jing-yu Zhang; Hua Tian; Ling-na Tang; Ai-lin Li (Journal of Zhejiang University-SCIENCE B, 2020)

Disseminated Mucormycosis Due to Saksenaea vasiformis Complex in an Immunocompetent Adult with Sustained Response to Posaconazole Treatment - Wee Liang En; Tan Seow Yen; Tan Ai Ling; Tan Yen Ee; Tan Sze Hwa; Ang Chia Chun; Santosa Anindita; Raymond Fong (Mycopathologia, 2020)

Cognitive Load of Exercise Influences Cognition and Neuroplasticity of Healthy Elderly: An Exploratory Investigation - Yi-Ping Chao; Changwei W. Wu; Li-Jung Lin; Cheng-Hung Lai; Hong-Yi Wu; Ai-Ling Hsu; Chiao-Nan Chen (Journal of Medical and Biological Engineering, 2020)
This study explored the effects of exercise with either high cognitive load or low cognitive load on cognitive performance and neuroplasticity in healthy elderly. Twenty-eight sedentary community-dwelling seniors participated in this study. Participants were assigned to one of three groups: the control group (C), low-cognitive load exercise group (LE), or high-cognitive load exercise group (HE). Individuals in both exercise groups engaged in moderate-intensity aerobic exercise for 4 months. Resting-state functional MRI and diffusion MRI were used to investigate the effects of intervention on functional and structural connectivity, respectively. Analysis of covariance with baseline, age and the education year as covariates was used to determine the effects of intervention. We found 4 months of exercise with high-cognitive load, but not exercise with low-cognitive load, improved the overall cognitive function of healthy elderly. Additionally, the HE group showed increased resting-state functional connectivity of superior frontal gyrus and anterior cingulate cortex and decreased functional connectivity of middle occipital gyrus and postcentral gyrus. The age-related alterations in local efficiency and betweenness were protected by exercise. Our findings might suggest that exercise with greater cognitive load likely results in greater training effects on cognition and brain connectivity than exercise requiring lower cognitive loads for healthy elderly.

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Triclosan induces zebrafish neurotoxicity by abnormal expression of miR-219 targeting oligodendrocyte differentiation of central nervous system - Yuhang Ling; Limei Sun; Danting Wang; Jiahui Jiang; Wenjing Sun; Weiming Ai; Xuedong Wang; Huili Wang (Archives of Toxicology, 2020)

Composition and change in the microbiome of Diaphorina citri infected with Candidatus Liberibacter asiaticus in China - Xiao-bing Song; Ai-tian Peng; Jin-feng Ling; Yi-ping Cui; Bao-ping Cheng; Lian-hui Zhang (International Journal of Tropical Insect Science, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

Leaf transcriptome of oil palm (Elaeis guineensis Jacq.) infected by Ganoderma boninense - Chai-Ling Ho; Yung-Chie Tan; Keat-Ai Yeoh; Wei-Kang Lee; Ahmad-Kamal Ghazali; Wai-Yan Yee; Chee-Choong Hoh (Trees, 2019)

First report of bovine viral diarrhea virus and Mycobacterium avium subspecies paratuberculosis infection in Tibetan sheep (Ovis aries) in Tibetan Plateau, China - Jian-Gang Ma; Ai-Ling Tian; Wen-Bin Zheng; Yang Zou; Yu-Ti Zhang; Zeng-Qi Yang (Tropical Animal Health and Production, 2019)

Macrophage-derived CCL18 promotes osteosarcoma proliferation and migration by upregulating the expression of UCA1 - Yang Su; Yan Zhou; Yuan-jue Sun; Ya-Ling Wang; Jun-yi Yin; Yu-jing Huang; Jian-jun Zhang; Ai-na He; Kun Han; Hui-zhen Zhang; Yang Yao; Xiao-Bin Lv; et al. (Journal of Molecular Medicine, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

The Influence of Seaweed Composite Flour on the Physicochemical Properties of Muffin - Hasmadi Mamat; Jahurul Md. Haque Akanda; Mohamad Khairi Zainol; Yu Ai Ling (Journal of Aquatic Food Product Technology, 2018)

Inflammatory Changes in Paravertebral Sympathetic Ganglia in Two Rat Pain Models - Ai-Ling Li; Jing-Dong Zhang; Wenrui Xie; Judith A. Strong; Jun-Ming Zhang (Neuroscience Bulletin, 2018)

Protective Effect of Selenoprotein X Against Oxidative Stress-Induced Cell Apoptosis in Human Hepatocyte (LO2) Cells via the p38 Pathway - Jia-Yong Tang; Ai-Hua He; Gang Jia; Guang-Mang Liu; Xiao-Ling Chen; Jing-Yi Cai; Hai-Ying Shang; Jin-Qiu Liao; Hua Zhao (Biological Trace Element Research, 2018)

Seasonal variability in bacterial and fungal diversity and community composition of the near-surface atmosphere in coastal megacity - Ai-ling Xu; Zhi-wen Song; Xiu-lu Lang; Xiang Chen; Yan Xia (Aerobiologia, 2017)

Laboratory investigations of earthquake- and landslide-induced composite surges - Hong-zhou Ai; Ling-kan Yao; Yi-liang Zhou (Journal of Mountain Science, 2017)

Functional characterization of the promoter of carbonyl reductase 1 gene in porcine endometrial cells - Ai-ling Zhang; Xian-yue Sun; Qi Yin; Jian-hua Zeng; Zhe Zhang; Jia-qi Li; Hao Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Effect of drying environment on engineering properties of an expansive soil and its microstructure - Ling-wei Kong; Min Wang; Ai-guo Guo; Yong Wang (Journal of Mountain Science, 2017)

Two new dammarane-type triterpenoid saponins from ginseng medicinal fungal substance - Wei Xu; Jin-hui Zhang; Xin Liu; Ai-ling Jia; Xiao-li Liu; Xin-wen Wang; Zhi-dong Qiu (Natural Product Research, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Effects of DDIT4 in Methamphetamine-Induced Autophagy and Apoptosis in Dopaminergic Neurons - Bing Li; Rui Chen; Ling Chen; Pingming Qiu; Xiuyun Ai; Enping Huang; Weiye Huang; Chuanxiang Chen; Chao Liu; Zhoumeng Lin; Wei-Bing Xie; Huijun Wang (Molecular Neurobiology, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

Stimulation of the ventral tegmental area increased nociceptive thresholds and decreased spinal dorsal horn neuronal activity in rat - Ai-Ling Li; Jiny E. Sibi; Xiaofei Yang; Jung-Chih Chiao; Yuan Bo Peng (Experimental Brain Research, 2016)

Cochliomycin A inhibits the larval settlement of Amphibalanus amphitrite by activating the NO/cGMP pathway - Kai-Ling Wang; Gen Zhang; Jin Sun; Ying Xu; Zhuang Han; Ling-Li Liu; Chang-Lun Shao; Qing-Ai Liu; Chang-Yun Wang; Pei-Yuan Qian (Biofouling, 2016)

Effects of metal-contaminated soils on the accumulation of heavy metals in gotu kola (Centella asiatica) and the potential health risks: a study in Peninsular Malaysia - Ghim Hock Ong; Ling Shing Wong; Ai Li Tan; Chee Kong Yap (Environmental Monitoring and Assessment, 2016)

Anatomic Structure and Expression Profiles of Related Genes: Novel Insights into Leaf Development in Celery - Xiao-Ling Jia; Guang-Long Wang; Feng Wang; Yan Li; Zhi-Sheng Xu; Ai-Sheng Xiong (Journal of Plant Growth Regulation, 2015)

Sequencing, assembly, annotation, and gene expression: novel insights into the hormonal control of carrot root development revealed by a high-throughput transcriptome - Guang-Long Wang; Xiao-Ling Jia; Zhi-Sheng Xu; Feng Wang; Ai-Sheng Xiong (Molecular Genetics and Genomics, 2015)

Response of the microbial community to seasonal groundwater level fluctuations in petroleum hydrocarbon-contaminated groundwater - Ai-xia Zhou; Yu-ling Zhang; Tian-zi Dong; Xue-yu Lin; Xiao-si Su (Environmental Science and Pollution Research, 2015)

Microbiology and audit of vascular access-associated bloodstream infections in multi-ethnic Asian hemodialysis patients in a tertiary hospital - Li Wen Loo; Yi Xin Liew; Hui Lin Lina Choong; Ai Ling Tan; Piotr Chlebicki (Infectious Diseases, 2015)

Comparative analysis of selected innate immune-related genes following infection of immortal DF-1 cells with highly pathogenic (H5N1) and low pathogenic (H9N2) avian influenza viruses - Ai-ling Liu; Yu-feng Li; Wenbao Qi; Xiu-li Ma; Ke-xiang Yu; Bing Huang; Ming Liao; Feng Li; Jie Pan; Min-xun Song (Virus Genes, 2015)

Myosin II regulates actin rearrangement-related structural synaptic plasticity during conditioned taste aversion memory extinction - Ai-Ling Bi; Yue Wang; Shuang Zhang; Bo-Qin Li; Zong-Peng Sun; Hong-Sheng Bi; Zhe-Yu Chen (Brain Structure and Function, 2015)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

Design and synthesis of tacrine-phenothiazine hybrids as multitarget drugs for Alzheimer’s disease - Ai-ling Hui; Yan Chen; Shi-jing Zhu; Chang-sheng Gan; Jian Pan; An Zhou (Medicinal Chemistry Research, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Profiling of differentially expressed genes in ectomycorrhizal fungus Pisolithus tinctorius responding to mycorrhiza helper Brevibacillus reuszeri MPt17 - Ai-Dong Zhou; Xiao-Qin Wu; Lan Shen; Xu-Ling Xu; Lin Huang; Jian-Ren Ye (Biologia, 2014)

The Effect of Energy Substrates on PHB Accumulation of Acidiphilium cryptum DX1-1 - Ai-ling Xu; Jin-lan Xia; Zhi-wen Song; Peng Jiang; Yan Xia; Min-xi Wan; Rui-yong Zhang; Yi Yang; Ke-ke Liu (Current Microbiology, 2013)

Genetic diversity and evolutionary characterization of Chinese porcine reproductive and respiratory syndrome viruses based on NSP2 and ORF5 - Jian-Kui Liu; Chun-Hua Wei; Xiao-Yan Yang; Xi-Lin Hou; AI-Ling Dai; Xiao-Hua Li; Mei-Kang Wei; Xiu-Zhen Pan (Archives of Virology, 2013)

Brain-targeting research of 10-O-nicotinate ginkgolide B: a new prodrug of ginkgolide B - Ze-Yu Wu; Jian Pan; Yuan Yuan; Ai-Ling Hui; Yi Yang; An Zhou; Min Tao; Xiao-Jian Zhou (Medicinal Chemistry Research, 2012)

Effect of polysaccharides extract of rhizoma atractylodis macrocephalae on thymus, spleen and cardiac indexes, caspase-3 activity ratio, Smac/DIABLO and HtrA2/Omi protein and mRNA expression levels in aged rats - Ling Guo; Yong Le Sun; Ai Hong Wang; Chong En Xu; Meng Yuan Zhang (Molecular Biology Reports, 2012)

A novel model to predict O-glycosylation sites using a highly unbalanced dataset - Kun Zhou; Chunzhi Ai; Peipei Dong; Xuran Fan; Ling Yang (Glycoconjugate Journal, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

Effects of ghrelin gene genotypes on the growth traits in Chinese cattle - Ai-ling Zhang; Li Zhang; Liang-zhi Zhang; Cun-fang Zhang; Xian-yong Lan; Chun-lei Zhang; Hong Chen (Molecular Biology Reports, 2012)

Lanthanide Salts of Heteropoly Molybdotungstosilicate LnHSiMo10W2O40·xH2O (Ln = Pr, Nd, Sm, Gd, Tb, Dy, Yb) Binding to Bovine Serum Albumin: A Fluorescence Quenching Study - Ai-Min Bai; Yu Ou-Yang; Hua-Li Yue; Xiao-Ling Li; Yan-Jun Hu (Biological Trace Element Research, 2012)

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

Profiling the differentially expressed genes in two rice varieties during rapid grain-filling stages - Chin-Jit Teo; Le Vinh Thuc; Keat-Ai Yeoh; Wai-Sun Chan; Sudha V. Chivukula; Parameswari Namasivayam; Chai-Ling Ho (Acta Physiologiae Plantarum, 2011)

Molecular identification of house dust mites and storage mites - Shew Fung Wong; Ai Ling Chong; Joon Wah Mak; Jessie Tan; Suk Jiun Ling; Tze Ming Ho (Experimental and Applied Acarology, 2011)

Relationship between HPLC fingerprints and in vivo pharmacological effects of a traditional Chinese medicine: Radix Angelicae Dahuricae - Hong Nie; Hui Zhang; Xiao-qi Zhang; Yong Luo; Lan-zhen Meng; Zhen Yin; Jianyu Zhang; Kongyan Li; Ai-hua Xiong; Ling Zhong; Heqing Huang; Wen-cai Ye (Natural Product Research, 2011)

Follicle-stimulating hormone promotes proliferation of cultured chicken ovarian germ cells through protein kinases A and C activation - Hong-yun Liu; Wei-dong Zeng; Ai-ling Cao; Cai-qiao Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Functional evaluation of therapeutic response for a mouse model of medulloblastoma - Aislynn K. Samano; Sachiko Ohshima-Hosoyama; Thomas G. Whitney; Suresh I. Prajapati; Aoife Kilcoyne; Eri Taniguchi; William W. Morgan; Laura D. Nelon; Ai-Ling Lin; Osamu Togao; Inkyung Jung; Brian P. Rubin; et al. (Transgenic Research, 2010)

Fractions and leaching characteristics of mercury in coal - Chun-Gang Yuan; Qing-Peng Li; Ya-Na Feng; Ai-Ling Chang (Environmental Monitoring and Assessment, 2010)

A one-step real-time reverse transcription-polymerase chain reaction detection of classical swine fever virus using a minor groove binding probe - Guoyuan Wen; Jun Yang; Qingping Luo; Zhibin Hu; Nianhua Song; Rongrong Zhang; Hongling Wang; Diyun Ai; Ling Luo; Huabin Shao (Veterinary Research Communications, 2010)

Expression Profiles of Class A Rice Heat Shock Transcription Factor Genes Under Abiotic Stresses - Ai-Ling Liu; Jie Zou; Xian-Wen Zhang; Xiao-Yun Zhou; Wen-Fang Wang; Xing-Yao Xiong; Li-Yun Chen; Xin-Bo Chen (Journal of Plant Biology, 2010)

Heavy metal concentrations of agricultural soils and vegetables from Dongguan, Guangdong - Limei Cai; Lanchun Huang; Yongzhang Zhou; Zhencheng Xu; Xiaochun Peng; Ling’ai Yao; Yang Zhou; Ping’an Peng (Journal of Geographical Sciences, 2010)

Biogeochemical transfer and dynamics of iodine in a soil–plant system - Huan-Xin Weng; Ai-Lan Yan; Chun-Lai Hong; Ya-Chao Qin; Lehua Pan; Ling-Li Xie (Environmental Geochemistry and Health, 2009)

Micro-Electrocardiograms to Study Post-Ventricular Amputation of Zebrafish Heart - Ping Sun; Yolanda Zhang; Fei Yu; Elizabeth Parks; Althea Lyman; Qiong Wu; Lisong Ai; Chang-Hong Hu; Qifa Zhou; Kirk Shung; Ching-Ling Lien; Tzung K. Hsiai (Annals of Biomedical Engineering, 2009)

Mechanism of Iodine Uptake by Cabbage: Effects of Iodine Species and Where It is Stored - Huan-Xin Weng; Chun-Lai Hong; Ai-Lan Yan; Le-Hua Pan; Ya-Chao Qin; Lü-Ting Bao; Ling-Li Xie (Biological Trace Element Research, 2008)

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

Mechanisms of lysosomal proteases participating in cerebral ischemia-induced neuronal death - Ai-Ping Qin; Hui-Ling Zhang; Zheng-Hong Qin (Neuroscience Bulletin, 2008)

Altered gene expression of NIDD in dorsal root ganglia and spinal cord of rats with neuropathic or inflammatory pain - Meng-Ling Chen; Chun Cheng; Qing-Shan Lv; Zhi-Qin Guo; Ying Gao; Shang-Feng Gao; Xin Li; Shu-Qiong Niu; Shu-Xian Shi; Ai-Guo Shen (Journal of Molecular Histology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Improvement of Expression Level and Bioactivity of Soluble Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (Apo2L/TRAIL) by a Novel Zinc ion Feeding Strategy - Ai-You Sun; Ya-Ling Shen; Ji-Cheng Yin; Hong Zhang; Ya-Nan Tang; Dong-Zhi Wei (Biotechnology Letters, 2006)

Effects of chloride and potassium channel blockers on apoptotic cell shrinkage and apoptosis in cortical neurons - Ling Wei; Ai Ying Xiao; Chun Jin; Aizhen Yang; Zhong Yang Lu; Shan Ping Yu (Pflügers Archiv - European Journal of Physiology, 2004)

High-level production of soluble tumor necrosis factor-related apoptosis-inducing ligand (Apo2L/TRAIL) in high-density cultivation of recombinant Escherichia coli using a combined feeding strategy - Ya-Ling Shen; Yue Zhang; Ai-You Sun; Xiao-Xia Xia; Dong-Zhi Wei; Sheng-Li Yang (Biotechnology Letters, 2004)

Characterization of soybean genomic features by analysis of its expressed sequence tags - Ai-Guo Tian; Jun Wang; Peng Cui; Yu-Jun Han; Hao Xu; Li-Juan Cong; Xian-Gang Huang; Xiao-Ling Wang; Yong-Zhi Jiao; Bang-Jun Wang; Yong-Jun Wang; Jin-Song Zhang; et al. (Theoretical and Applied Genetics, 2004)

Urinary homovanillic acid (HVA) and vanillymandelic acid (VMA) in workers exposed to manganese dust - Ling Bao Ai; Lay Ha Chua; Ai Li New; Bee Lan Lee; Yi Mim Liu; Sin Eng Chia; Choon Nam Ong (Biological Trace Element Research, 1998)